A novel nomogram for the preoperative prediction of sentinel lymph node metastasis in breast cancer. (15th December 2022) - Wang, Xue‐fei; Zhang, Guo‐chao; Zuo, Zhi‐chao; Zhu, Qing‐li; Liu, Zhen‐zhen; Wu, Sha‐fei; Li, Jia‐xin; Du, Jian‐hua; Yan, Cun‐li; Ma, Xiao‐ying; Shi, Yue; Shi, He; et al.
Abstract: Background or Purpose: A practical noninvasive method to identify sentinel lymph node (SLN) status in breast cancer patients, who had a suspicious axillary lymph node (ALN) at ultrasound (US), but a negative clinical physical examination is needed. To predict SLN metastasis using a nomogram based on US and biopsy‐based pathological features, this retrospective study investigated associations between clinicopathological features and SLN status. Methods: Patients treated with SLN dissection at four centers were apportioned to training, internal, or external validation sets ( n  = 472, 175, and 81). Lymph node ultrasound and pathological characteristics were compared using chi‐squared and t ‐tests. A nomogram predicting SLN metastasis was constructed using multivariate logistic regression models. Results: In the training set, statistically significant factors associated with SLN + were as follows: histology type ( p  < 0.001); progesterone receptor (PR: p  = 0.003); Her‐2 status ( p  = 0.049); and ALN‐US shape ( p  = 0.034), corticomedullary demarcation (CMD: p  < 0.001), and blood flow ( p  = 0.001). With multivariate analysis, five independent variables (histological type, PR status, ALN‐US shape, CMD, and blood flow) were integrated into the nomogram (C‐statistic 0.714 [95% CI: 0.688–0.740]) and validated internally (0.816 [95% CI: 0.784–0.849]) and externally (0.942 [95% CI: 0.918–0.966]), with good predictive accuracy and clinical applicability. Conclusion: This nomogram could be a direct and reliable tool for individual preoperative evaluation of SLN status, and therefore aids decisions concerning ALN dissection and adjuvant treatment. Abstract : This nomogram is using pathology and ultrasound parameters preoperatively to predict SLN metastasis. Cindex, calibration, discrimination, and clinical use of the nomogram show well in the training, internal and external validation sets.